2017
DOI: 10.1093/mnras/stx3200
|View full text |Cite
|
Sign up to set email alerts
|

Individual stellar haloes of massive galaxies measured to 100 kpc at 0.3 < z < 0.5 using Hyper Suprime-Cam

Abstract: Massive galaxies display extended light profiles that can reach several hundreds of kilo parsecs. These stellar halos provide a fossil record of galaxy assembly histories. Using data that is both wide (∼100 deg 2 ) and deep (> 28.5 mag arcsec −2 in i-band), we present a systematic study of the stellar halos of a sample of more than 3000 galaxies at 0.3 < z < 0.5 with log M /M > 11.4. Our study is based on high-quality (0.6 seeing) imaging data from the Hyper Suprime-Cam (HSC) Subaru Strategic Program (SSP), wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
133
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(147 citation statements)
references
References 166 publications
(271 reference statements)
12
133
1
1
Order By: Relevance
“…Huang et al (2018) converted the observed surface brightness to stellar mass assuming that the massive galaxies can be well described by an average stellar mass to light ratio. Huang et al (2018) achieved SED fitting and K-correction using the five-band HSC cModel magnitudes. In our analysis, we choose to focus on the surface brightness instead of looking at the stellar mass mainly because of the following reasons.…”
Section: Isolated Central Galaxiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al (2018) converted the observed surface brightness to stellar mass assuming that the massive galaxies can be well described by an average stellar mass to light ratio. Huang et al (2018) achieved SED fitting and K-correction using the five-band HSC cModel magnitudes. In our analysis, we choose to focus on the surface brightness instead of looking at the stellar mass mainly because of the following reasons.…”
Section: Isolated Central Galaxiesmentioning
confidence: 99%
“…The shapes and amplitudes of stellar haloes for in-dividual galaxies show large diversities (e.g. Harmsen et al 2017;Huang et al 2018), reflecting the stochastic of merging histories. Using the high-resolution Illustris simulation, Pillepich et al (2014) investigated the logarithmic slopes of spherically averaged stellar density profiles for galaxies at z = 0.…”
Section: Universality Of Stellar Haloesmentioning
confidence: 99%
“…The subsequent evolution is dominated by assembly of stellar halos by dissipationless minor (dry) mergers (e.g., Khochfar & Silk 2006;Naab et al 2006;Oser et al 2010Oser et al , 2012Johansson et al 2012;Hilz et al 2013). This two-phase formation scenario provides an explanation for the observed growth in the ef-fective radii (e.g., Newman et al 2012;van der Wel et al 2014) and stellar halos of massive galaxies (e.g., Szomoru et al 2012;Patel et al 2013;Huang et al 2018).…”
Section: Introductionmentioning
confidence: 88%
“…Indeed, observed stellar mass fractions and stellar mass function of cluster galaxies have become valuable benchmarks for testing models of feedback in cosmological simulations of cluster formation (e.g., Martizzi et al 2014Martizzi et al , 2016Bahé et al 2017;McCarthy et al 2017;Cui et al 2018;Pillepich et al 2018;Henden et al 2018). The radial profile of stellar density of the Brightest Cluster Galaxy (BCG), as well as the radial distribution of stellar mass in galaxies are potentially equally powerful constraints on the models (e.g., Martizzi et al 2014;Bellstedt et al 2018).Despite recent progress (Gonzalez et al 2013;Budzynski et al 2012Budzynski et al , 2014Kravtsov et al 2018;Huang et al 2018), the number of clusters with available accurate measurements of the gas mass, stellar mass in galaxies down to dwarf scales, and stellar material in the outer envelope of the central galaxy remains small. The main goal of this study is to accurately measure the contribution of the stellar populations (individual galaxies and intra-cluster light) to the total baryon budget in the cluster Abell 133.Abell 133 is a massive nearby (z = 0.05695) galaxy cluster with extensive mapping of surrounding distribution of galaxies and filamentary cosmic web structure (Connor et al 2018(Connor et al , 2019b, as well as deep X-ray observations by the Chandra X-ray Observatory (Vikhlinin et al 2006;Vikhlinin 2013; Morandi & Cui 2014, Vikhlinin et al, in preparation).…”
mentioning
confidence: 99%
“…Despite recent progress (Gonzalez et al 2013;Budzynski et al 2012Budzynski et al , 2014Kravtsov et al 2018;Huang et al 2018), the number of clusters with available accurate measurements of the gas mass, stellar mass in galaxies down to dwarf scales, and stellar material in the outer envelope of the central galaxy remains small. The main goal of this study is to accurately measure the contribution of the stellar populations (individual galaxies and intra-cluster light) to the total baryon budget in the cluster Abell 133.…”
mentioning
confidence: 99%